Analisis Kinerja Agribisnis Stroberi di Kabupaten Bandung - Fitri Sulis Setiawati; Yosini Deliana; Trisna Insan Noor (Universitas Galuh, 2026)
Strawberry is a high-value horticultural commodity in Bandung Regency (Ciwidey–Rancabali), yet its highly perishable nature makes end-to-end agribusiness performance critical. This study aims to evaluate strawberry agribusiness performance across five subsystems (input supply, on-farm production, harvest–postharvest handling, marketing, and supporting institutions) and to identify priority bottlenecks for improvement. A mixed-methods design was applied by combining a structured survey, in-depth interviews, and field observations. Using cluster random sampling, 100 strawberry farmers were selected from Alamendah and Sukaresmi Villages, Rancabali District. Performance indicators were assessed using a five-point Likert scale, converted into interval data through the Method of Successive Interval (MSI), and interpreted using a tiered categorization. The results indicate an overall agribusiness performance score of 2.34, categorized as “fair”. The input subsystem achieved the highest score (2.58), followed by marketing (2.45) and supporting institutions (2.42), whereas production (2.18) and harvest–postharvest handling (2.11) were the weakest subsystems. Major constraints included high input prices, limited adoption of cultivation technologies, inadequate storage and processing practices, low diversification of marketing channels, and weak farmer-group participation and perceived government support. Strengthening cultivation technology, upgrading postharvest management (cooling, storage, and processing), expanding market outlets, and revitalizing farmer institutions are essential to improve performance from “fair” to “good”.